Unraveling enhanced activity and coke resistance of Pt-based catalyst in bio-aviation fuel refining. (1st November 2021) - Yang, Huiru; Du, Xiangze; Lei, Xiaomei; Zhou, Keyao; Tian, Yunfei; Li, Dan; Hu, Changwei
Graphical abstract: Highlight: A high bio-aviation fuel yield (63.5%) was obtained on 2%Pt/50%SAPO-11-50%γ-Al2 O3. The obtained bio-aviation fuel had similar properties to commercial jet fuel. The composite carrier catalyst exhibited better coke resistance compared to single ones. The composite carrier was conducive to the generation of Pt with small particle size. Abstract: Carbon deposition seriously affects the stability of catalyst, which restricts the industrialization of the one-step process for refining bio-aviation fuel. Pt supported on 50%SAPO-11-50%γ-Al2 O3 composite carrier was designed and synthesized, which presented enhanced coke resistance. The bio-aviation fuel with similar properties to the commercial jet fuel was obtained with a high yield of 63.5%. A series of characterization methods (including TG, XRD, H2 -TPR, NH3 -TPD, Py-IR, XPS, TEM and CO-pulse chemisorption) were utilized to reveal the structure characteristics of catalysts. TEM and CO-pulse chemisorption analysis indicates that the composite carrier is favorable for the dispersion of Pt with small active particles generated. The results from XPS, XRD and H2 -TPR shows that the different ratios of Pt 0 /Pt 4+ are generated due to the different interaction between Pt species and carriers. Py-IR results display that the composite carrier provides proper amount of Brønsted acid and Lewis acid sites correlated with the high bio-aviation fuel yield and enhanced coke resistance. The metallic platinum (Pt 0 ) promotes the formation of Brønsted acid sites on catalysts, where excesses Brønsted acid sites causing the olefin polymerization, and inducing the formation of carbon deposition. The study offers an effective strategy to design the catalyst with excellent coke resistance by composite carrier effect toward refining bio-aviation fuel.